Virtual Subspace-Based DTC Strategy for Torque Ripple Minimization in Six-Phase Induction Motors - Mohammad Hosein Holakooie (IEEE, 2021)
Classical switching-table-based direct torque control (ST-DTC) of six-phase induction machine (6PIM) drives is seriously penalized by current harmonics as well as torque ripples because of uncontrolled voltage vectors in the low-impedance non-energy subspace and hysteresis torque regulator, respectively. Hence, a virtual subspace-based DTC strategy is proposed to alleviate the impact of low-order current harmonics and torque ripples. The proposed virtual subspace includes 48 virtual voltage vectors (VVs) in the $α -β $ subspace with average volt-seconds of zero in the $z_{1}-z_{2}$ subspace, which offers full extent of freedom degrees for 6PIM fed by a two-level voltage source inverter (VSI). The increased number of VVs allows the possibility to design up to nine-level hysteresis torque regulator to minimize the torque ripples. Nevertheless, in this paper, it is found that torque ripple, current harmonics, average switching frequency, and computational burden come to a compromise with a seven-level hysteresis torque regulator. The impact of these VVs on the performance of ST-DTC is experimentally studied and some details of hardware implementation are presented. The performance of the proposed scheme is verified by simulations as well as laboratory experiments, where a complete comparison with recent schemes is made to reveal the superiority of the proposed scheme.